1976
DOI: 10.1044/jshr.1902.225
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyographic Study of Velopharyngeal Function in Speech

Abstract: Electromyographic (EMG) recordings were obtained from the levator palatini, superior pharyngeal constrictor, middle pharyngeal constrictor, palatoglossus, and palatopharyngeus muscles of three talkers of American English. Bipolar hooked-wire electrodes were used. Each subject read nonsense words composed of three vowels (/i, a, u/), six stop consonants (/p, b, t, d, k, g/), and two nasal consonants (/m, n/) to form various stop-nasal and nasal-stop contrasts. Multiple repetitions of each utterance type were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
3

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 0 publications
5
43
1
3
Order By: Relevance
“…This tight seal prevents nasal leakage and creates the aerodynamic conditions necessary for obstruency. The inclusion of a velum closure gesture for obstruents is supported by experimental results that show raising of the velum during the production of oral stops, even when surrounded by oral vowels (Lubker 1968;Bell-Berti & Hirose 1975;Bell-Berti 1976).…”
Section: Coactivation Transparencymentioning
confidence: 70%
“…This tight seal prevents nasal leakage and creates the aerodynamic conditions necessary for obstruency. The inclusion of a velum closure gesture for obstruents is supported by experimental results that show raising of the velum during the production of oral stops, even when surrounded by oral vowels (Lubker 1968;Bell-Berti & Hirose 1975;Bell-Berti 1976).…”
Section: Coactivation Transparencymentioning
confidence: 70%
“…The primary muscle responsible for elevating the velum is the levator veli palatini (Bell-Berti, 1976;BellBerti, 1993) which is innervated by the mandibular branch of the trigeminal nerve (cranial nerve V) (Seikel, King, & Drumright, 1997). The tensor veli palatini, musculus uvulae, palatoglossus, and palatopharyngeus muscles also play a role in changing the shape and position of the velum (Seikel et al, 1997).…”
Section: Velar Anatomy and Physiologymentioning
confidence: 99%
“…Specifically, vowels produced with high tongue position are accompanied with a higher velum and greater VP closure force than vowels produced with lower tongue position (Bell-Berti, 1976;Bell-Berti & Krakow, 1991;Moon, Kuehn & Huisman, 1994;Kuehn & Moon, 1998). In a cineflorographic study, Moll (1962) investigated the variation of VP closure as a function of the vowel produced as well as the consonant environment of the vowel in 10 normal adult speakers during their production of CVC syllables containing the vowels /i/, /ae/, /a/ and /u/.…”
Section: Velopharyngeal Coarticulation and Vowel Heightmentioning
confidence: 99%
“…The relationship between tongue height and velum height is one of the most documented phonetic factors influencing VP function (Moll, 1962;Moll & Shriner, 1967;Lubker, 1968;Fritzell, 1969;Ohala, 1971;Bell-Berti, 1976;Clumeck, 1976;Bell-Berti, Baer, Harris & Niimi, 1979;Al-Bamerni, 1983;Henderson, 1984;Bell-Berti & Krakow, 1991;Kuehn & Moon, 1998). Bell-Berti (1993) reported that the velum position varies systematically as a function of the phonetic contexts; she explains that "velic position is lowest for nasal consonant, somewhat higher for low vowels, higher still for high vowels, and highest for obstruent consonant" (p.69).…”
Section: Velopharyngeal Coarticulation and Vowel Heightmentioning
confidence: 99%
See 1 more Smart Citation